STUDENTS’ PERSPECTIVES ON THE USE OF EDMODO IN ‘INTERMEDIATE LISTENING’ CLASS AT STKIP PGRI SIDOARJO - J Priyanto Widodo; Endah Alam Sari (Magister Scientiae, 2022)
The purpose of this study was to ascertain students’ perspectives toward the use of Edmodo in the 'Intermediate Listening' class of the English Education Study Program at STKIP PGRI Sidoarjo. To accomplish the objective, the researcher employed a questionnaire as the primary instrument and a descriptive quantitative design. The researcher surveyed 37 respondents using 13 closed-ended questionnaires. The questionnaire was divided into three sections. Edmodo as an effective tool in writing class, Edmodo as a Supplementary tool in 'Intermediate Listening' class, and Edmodo as a Supplementary Tool for Learning. The questionnaires were adapted from those used in Manowong (2016). On the basis of the data collected, it can be concluded that: (a) Edmodo is an effective and beneficial tool for teaching and learning English, particularly in the 'Intermediate Listening' class. (b) Edmodo enables lecturers to monitor and maintain their students' progress. (c) Edmodo provides a snapshot of students' progress and accomplishments. Additionally, the results indicated that the majority of students agreed that explanations, quizzes, and other online tasks provided by the lecturer in Edmodo assist students in improving their learning and comprehension of the 'Intermediate Listening' course. The internet-based reference materials, such as links to materials, videos, images, and articles posted by the lecturer, assist students in comprehending the course. Edmodo is one of the most innovative and creative supplemental teaching methods available for enhancing classroom interaction.